The Effect of Environment and Parental Teaching on the Formation of Adolescent Morales and Behavior - Ahmad Munawar, Niknik (Greenation Publisher & Yayasan Global Research National, 2023)
Literature articles are articles used to create research hypotheses about relationships between variables that will be used in further research within the framework of. The writing method of this literature review article is the library search method from online media such as Google Scholar, Mendeley and other online academic media. The findings of this literature review article are: 1) the environment affects adolescents’ morals and behaviors; 2) parenting affects adolescents’ morals and behaviors; in addition to these two exogenous variables affecting attitudes and behaviors endogenous variables, there are other factors, including associations, mindset, heredity, and heredity.